Features of the fluctuation of the ephemerous-ephemeroid synusion in the semidesert phytocenosis of the Kura-Araz lowland in connection with climatic changes - Gasimova, Khatira G.; Abdiyeva, Rena T.; Ali-zade, Valida M. (Journal of the Belarusian State University. Ecology, 2022)
The dynamics of semi-desert herbaceous phytocenoses was studied under the conditions of the Kura-Araz lowland on permanent model sites (10x10 m). Based on seven-year (2014-2020) stationary observations, regularities of seasonal and annual fluctuations of cereal-forb and legume-forb phytocenoses were revealed in connection with weather conditions. The analysis of data on the longterm dynamics of their species composition, structure, stock of the raw above-ground part is carried out. The a-diversity is estimated by generally accepted indices, the results of phenological observations are given. It was found that in the seasonal dynamics of plants, the beginning of the growing season depends on the air temperature in March, and the end of the cycle depends on the air temperature in May-early June. The optimal dates for the mass development of grasses are the beginning and the middle of May. In the case of an increased norm of atmospheric precipitation and a late onset of summer heat, this pattern may be violated, and the dates are shifted to the end of May - beginning of June. Over the years of observations in the cereal-forb phytocenosis of 19 species, 9, and in the legume-forb phytocenosis of 17 species, 5 turned out to be constant. The total projective cover ranged from 50 (dry years) to 100 % (wet years). The assessment of a-diversity showed that the species diversity of phytocenoses increased in years with a high amount of atmospheric precipitation in May. A linear dependence of phytomass on the total amount of atmospheric precipitation for March-June was revealed. It was found that the best accumulation of herbal phytomass is influenced by the amount of precipitation in late spring. The most resistant to warming plant species have been identified. These are mainly cereals with an average feed value: Avena eriantha, Bromus japonicus, Bromus rubens, Eremopyrum orientale, Lolium rigidum and weed herbs - Capsella bursa-pastoris, Carduus pycnocephalus, Convolvulus arvensis, Erodium cicutarium, Lepidium draba, Xanthium strumarium, the last species is an invasive plant. Among the representatives of legumes, only one species, Medicago minima, turned out to be relatively resistant to high air temperatures. It was found that of the total herbage, only 35.5 % of species can withstand a warming of 1.5-2 °C.
Keywords: arid territories; weather conditions; dominants; fluctuations; abundance; vegetation; mass development; a-diversity dynamics; phytomass dynamics